2020
DOI: 10.3389/fgene.2019.01292
|View full text |Cite
|
Sign up to set email alerts
|

Data-Mining Approach on Transcriptomics and Methylomics Placental Analysis Highlights Genes in Fetal Growth Restriction

Abstract: Intrauterine Growth Restriction (IUGR) affects 8% of newborns and increases morbidity and mortality for the offspring even during later stages of life. Single omics studies have evidenced epigenetic, genetic, and metabolic alterations in IUGR, but pathogenic mechanisms as a whole are not being fully understood. An in-depth strategy combining methylomics and transcriptomics analyses was performed on 36 placenta samples in a case-control study. Data-mining algorithms were used to combine the analysis of more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
(63 reference statements)
2
7
0
Order By: Relevance
“…All participants provided written informed consent prior to inclusion. The study was conducted in accordance with the declaration of Helsinki (Chabrun et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…All participants provided written informed consent prior to inclusion. The study was conducted in accordance with the declaration of Helsinki (Chabrun et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…They built machine learning models that had a high capacity for predicting PTB, with r 2 of 0.83 between the predicted and the actual PTB score. ( 184 ) Ghaemi et al, in 51 samples from 17 pregnant women who delivered at term, built multivariate predictive models for gestational age using the Elastic net algorithm to integrate the multi-omics datasets including transcriptomics, microbiomics, proteomics and metabolomics, which can significantly increase predictive power compared to models based on single-omics datasets. ( 185 ) However, as with the other types of studies reviewed above, these currently available studies had limited samples sizes, and their findings call for replication in large populations.…”
Section: Recent Advances In Multi-omics Studies Of Ptbmentioning
confidence: 99%
“…Genome-wide transcriptomic and epigenomic studies have greatly contributed to the understanding of the molecular mechanisms involved in either normal or pathological placenta development. Thus, numerous studies have revealed altered placental expression of various genes in PE and IUGR ( Cox et al, 2015 ; Deyssenroth et al, 2017 ; Chabrun et al, 2019 ; Majewska et al, 2019 ; Benny et al, 2020 ). A particular category concerns those genes encoding for non-protein coding RNAs (ncRNAs).…”
Section: Introductionmentioning
confidence: 99%